(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
With technological advancement and the spread of globalization, social media has become a prominent influence on the lives of individuals across all ages, penetrating all spaces, including the family sphere. Users now spend most of their time in front of screens, leading to internet addiction. From among these categories, we chose the adolescent category, which requires careful attention and monitoring, specifically secondary school students at AL SAHN high school in EL GHERRARA city. The aim was to measure the relationship between family harmony and internet addiction, using a descriptive approach and relying on the kimberly Young internet addiction scale and the Belmihoub Kalkhoum harmony family scale, along with statistical methods to test the study hypotheses.